The problem of value orientations in the teaching process - Orjonikidze, Nino; Akhvlediani, Maya; Abdaladze, Lali (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
People's values are largely determined by historical time, life cycle and personal characteristics. Morality occupies the most important place in the value orientations of a person. It concentrates with moral values and is conditioned by morality. Looking at the complexity of the problem, we realize that the teaching-pedagogical activity needs a lot of effort to establish the right orientations. Against the background of modern requirements and situations, it is desirable to give preference to the ultra-modern methods used in Western pedagogical practice, it is actually a system of methods that includes the entire educational process. We considered variant teaching of value-moral elements with different groups of students, representatives of different types of families and the implementation of related educational content as a concrete way of our task. Our trial-experimental activities have shown us that targeted pedagogical measures significantly accelerate the process of forming students' moral views.